2015
DOI: 10.1038/ejhg.2015.176
|View full text |Cite
|
Sign up to set email alerts
|

Reinitiation of mRNA translation in a patient with X-linked infantile spasms with a protein-truncating variant in ARX

Abstract: Mutations in the Aristaless-related homeobox gene (ARX) lead to a range of X-linked intellectual disability phenotypes, with truncating variants generally resulting in severe X-linked lissencephaly with ambiguous genitalia (XLAG), and polyalanine expansions and missense variants resulting in infantile spasms. We report two male patients with early-onset infantile spasms in whom a novel c.34G4T (p.(E12*)) variant was identified in the ARX gene. A similar variant c.81C4G (p.(Y27*)), has previously been described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…To determine the impact of serine phosphorylation on the function of the ARX protein, phospho-null substitutions were generated in which the serine residues identifed to be phosphorylated were replaced with alanines. Using a dual-luciferase reporter assay described in our previous work [ 20 , 21 ] we measured the impact of these mutations on the interaction with an orthologous Arx-binding site in the enhancer region of Lmo1 [ 22 ] inserted upstream of an SV40 promoter driving luciferase expression. Using this assay, we demonstrate that phosphorylation of serine residues identified in this study does not affect ARX transcriptional activity in HEK293T cells ( S6 Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…To determine the impact of serine phosphorylation on the function of the ARX protein, phospho-null substitutions were generated in which the serine residues identifed to be phosphorylated were replaced with alanines. Using a dual-luciferase reporter assay described in our previous work [ 20 , 21 ] we measured the impact of these mutations on the interaction with an orthologous Arx-binding site in the enhancer region of Lmo1 [ 22 ] inserted upstream of an SV40 promoter driving luciferase expression. Using this assay, we demonstrate that phosphorylation of serine residues identified in this study does not affect ARX transcriptional activity in HEK293T cells ( S6 Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, patients with PT variants leading to total loss-of-function (LOF) have more severe XLAG, whereas patients with polyalanine expansions generally have ISSX or a form of intellectual disability [Kato et al, 2004]. Recently, cousins with c.81C>G (p.Tyr27*) and two brothers with c.34G>T (p.Glu12*) in ARX were reported with ISSX [Fullston et al, 2010; Moey et al, 2016]; none had the clinical features of XLAG as would be expected from a total loss of functional protein. Both, the p.Tyr27* and the p.Glu12* pathogenic variants, reinitiated translation at p.M41 suggesting that an N-terminally truncated ARX partially rescued the more severe brain malformation phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Moey and col. [129] and Fullston and col. [121] have shown that certain missense variants early on in the ARX gene induce a premature termination of the protein (amino acid residue 12 or 27) in patients with early-onset infantile spasms. In these cases they show that a reinitiation of translation is possible (e.g.…”
Section: 213a Aristaless Related Homeobox (Arx) and Interneuronopmentioning
confidence: 99%